ANALISIS TINGKAT KETERCAPAIAN ANGKA PARTISIPASI SEKOLAH DI PAPUA (STUDI KASUS DI KABUPATEN MERAUKE) - Maharani, Kiki; Effendi, Moh. Mahfud; Nurjaman, Asep (Jurnal Kebijakan dan Pengembangan Pendidikan, 2019)
Abstract: School participation is integrally an effort to achieve quality education quality. This study aims to obtain information about (1) factors that influence the level of achievement and school participation rates, constraints in increasing enrollment rates. (2) the role of regional autonomy in improving the quality of education services. The approach used is a type of qualitative approach. Data collection techniques used in the form of interviews and documents and observation. The results showed that (1) Factors influencing the low number of school participation in Merauke Regency were access to education that was difficult to reach in remote areas, limited availability of teacher numbers and uneven distribution, teacher welfare that was still lacking, educational facilities that were not yet adequate in remote areas, the level of public education, and the slow attention of the government. (2) The role of regional autonomy in improving the quality of education services has not been maximized. The principle of justice, efficiency, transparency, and public accountability in efforts to improve and improve the quality and quantity of education becomes the responsibility and concern of all parties, both the government, regional governments, and the community.Keywords: Participation Rates, Level of Achievement, Education Abstrak: Partisipasi sekolah secara integral menjadi usaha dalam mencapai mutu pendidikan yang berkualitas. Penelitian ini bertujuan untuk memperoleh informasi tentang (1) faktor-faktor yang mempengaruhi tingkat ketercapaian dan angka partisipasi sekolah, kendala dalam peningkatan angka partisipasi. (2) peran otonomi daerah dalam peningkatan mutu pelayanan pendidikan. Pendekatan yang digunakan yaitu jenis pendekatan kualitatif. Teknik pengumpulan data yang digunakan berupa wawancara dan dokumen serta observasi. Hasil penelitian menunjukkan bahwa (1) Faktor-faktor yang mempengaruhi rendahnya angka partisipasi sekolah di Kabupaten Merauke yaitu akses pendidikan yang sulit dijangkau pada daerah terpencil, ketersediaan jumlah tenaga guru yang terbatas dan distribusinya kurang merata, kesejahteraan guru yang masih kurang, fasilitas pendidikan yang belum memadai di daerah terpencil, tingkat pendidikan masyarakat, serta lambannya perhatian dari pemerintah. (2) Peran otonomi daerah dalam peningkatan mutu pelayanan pendidikan belum maksimal. Prinsip keadilan, efisiensi, transparansi, dan akuntabilitas publik dalam upaya perbaikan dan peningkatan kualitas serta kuantitas pendidikan menjadi tanggung jawab dan perhatian bersama seluruh pihak, baik pemerintah, pemerintah daerah dan masyarakat.Kata kunci: Angka Partisipasi, Tingkat Ketercapaian, Pendidikan